Problematika Lembaga Pendidikan Islam di Era Digital: Tantangan dan Solusi - Ibrah Safirah; Herlini Puspika Sari; Muhammad Hisyam; Nazifah Fitri Annisa (Moral : Jurnal kajian Pendidikan Islam, 2025)
Islamic educational institutions play a crucial role in shaping students’ character based on Islamic values. However, the rapid development of the digital era presents both opportunities and challenges. This article aims to analyze the problems faced by Islamic educational institutions in adapting to the digital age and to offer practical solutions. The research identifies key issues such as outdated curricula, lack of professional human resources, limited digital infrastructure, and financial constraints. The findings suggest that to remain relevant, these institutions must integrate technology into the learning process, reform curriculum design, improve teachers' digital competencies, and ensure sustainable funding. This study emphasizes the importance of collaborative efforts between schools, families, governments, and society in ensuring the advancement of Islamic education in a digitalized world.